EKSISTENSI PENDIDIKANTRADISIONAL DALAM PELAKSANAAN TUGAS DAN LAYANAN KEPENDIDIKAN DI ERA MODERN - Haris, Abd (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2016)
The essence of an education is a process of changing the form of effort or attitude or code of conduct of a person or group in an effort to mature in humans through efforts to implement educational activities and teaching by way of sticking to the norms or customs that has lasted for a long time that happened generations. There are some patterns that have been presented by the history of education, the educational pattern that uses the traditional system, to some people identified with non-formal schools that are done through takhassus, regeneration, diploma and others. System used in traditional education is by looking at the past history as an inspiration or something to be grasped. The traditionalist roots of theological thinking is that people have to accept all of the terms and the plan of God that has been previously established. During the Classical Islamic education are grouped into two categories: formal institutions are characterized by exclusive and agency side (informal) (kuttab, shuffauh, halaqoh, qushur, council houses and mosques and clerics) and they have the characteristics of each. Orientation traditional education is a sacred task, to spread the religion. Preserving the teachings of Islam, strengthening all tauhidan, Focused on Islam Scientific Education, teacher-centered education, learning traditional education system, they still wear halaqoh system, bekumpul, clumped after it forward one by one.